CREATING A COMPETITIVE ENVIRONMENT IN THE DEVELOPMENT OF PRIVATE MEDICAL SERVICES IN NAMANGAN PROVINCE - Isakov Oybek Jamoliddinovich (Scholar Express Journal, 2022)
The article describes the development of private medical services in Namangan region and the peculiarities of the competitive environment in the field of medicine.
Keywords: Private Medicine; State; Competition; Bed